Tripping on utopia : Margaret Mead, the Cold War, and the troubled birth of psychedelic science - Breen, Benjamin, 1985- (Grand Central Publishing, Hachette Book Group, 2024)
""It was not the Baby Boomers who ushered in the first era of widespread drug experimentation. It was their parents." Far from the repressed traditionalists they are often painted as, the generation that survived the second World War emerged with a profoundly ambitious sense of social experimentation. In the '40s and '50s, transformative drugs rapidly entered mainstream culture, where they were not only legal, but openly celebrated. American physician John C. Lilly infamously dosed dolphins (and himself) with LSD in a NASA-funded effort to teach dolphins to talk. A tripping Cary Grant mumbled into a Dictaphone about Hegel as astronaut John Glenn returned to Earth. At the center of this revolution were the pioneering anthropologists-and star-crossed lovers-Margaret Mead and Gregory Bateson. Convinced the world was headed toward certain disaster, Mead and Bateson made it their life's mission to reshape humanity through a new science of consciousness expansion, but soon found themselves at odds with the government bodies who funded their work, whose intentions were less than pure. Mead and Bateson's partnership unlocks an untold chapter in the history of the twentieth century, linking drug researchers with CIA agents, outsider sexologists, and the founders of the Information Age. As we follow Mead and Bateson's fractured love affair from the malarial jungles of New Guinea to the temples of Bali, from the espionage of WWII to the scientific revolutions of the Cold War, a new origin story for psychedelic science emerges"--